The Effect of Village Fund Allocation on Economic Development in Sawang District, North Aceh Regency - Yeni Amelda; Umaruddin Umaruddin (Journal of Malikussaleh Public Economics, 2020)
This study aims to determine the impact of village fund allocations on economic development in Sawang North Aceh Regency Indonesia. This study uses secondary data obtained from the sub-district Head Office of Sawang sub-district, North Aceh in 2017-2018. The method of data analysis used is panel data analysis. The results showed that the of village funds allocation does not influence economic development in Sawang Sub-district, North Aceh Regency in 2017-2018. Keywords: village fund allocation, economic development.